2014
DOI: 10.13080/z-a.2014.101.013
|View full text |Cite
|
Sign up to set email alerts
|

Species ratio, spring emergence, population dynamics and damage of plum sawflies Hoplocampa minuta and H. flava in plum orchard

Abstract: An investigation of black plum sawfly (Hoplocampa minuta Christ, 1791) and yellow plum sawfly (Hoplocampa flava Linnaeus, 1761) populations using white sticky traps Rebell ® bianco was carried out in a plum orchard of Institute of Horticulture of Lithuanian Research Centre for Agriculture and Forestry from 2010 to 2012. A possibility to predict spring emergence of H. minuta and H. flava using temperature sum method, species ratio, main population parameters and relation between trap catches and infestation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The fully-fed larvae spin parchment-like cocoons in the soil, in which they hibernate as quiescent larvae, until pupating shortly before emergence. Prolonged diapause, of up to three winters, has been reported by several authors for minuta and testudinea (Hadzistevic 1959, Tamosiunas et al 2014. This is presumed to be an adaptation against the risk to a population's survival in years when very few or no fruits develop, e.g.…”
Section: Figurementioning
confidence: 87%
See 1 more Smart Citation
“…The fully-fed larvae spin parchment-like cocoons in the soil, in which they hibernate as quiescent larvae, until pupating shortly before emergence. Prolonged diapause, of up to three winters, has been reported by several authors for minuta and testudinea (Hadzistevic 1959, Tamosiunas et al 2014. This is presumed to be an adaptation against the risk to a population's survival in years when very few or no fruits develop, e.g.…”
Section: Figurementioning
confidence: 87%
“…the "pests", the sex-ratio has generally been observed to be close to 1:1, with a slight bias towards females (e.g. Tamosiunas et al 2014). Among the West Palaearctic species, brevis is clearly exceptional in being normally (or entirely?)…”
Section: Figurementioning
confidence: 99%
“…A good indicator of survival, the distribution of age classes, and the dynamics of insect populations (Sadoudi et al, 2011;Kraft and Vannouhuys, 2013), the sex ratio allows estimation and understanding of the effects of environmental conditions or the structure of the habitat during various stages of life history (Suarez-Coya, 2013). According to Tamošiūnas et al (2014), the determination of the sex ratio of an insect population is crucial to assess the conditions and status of this population, seasonal emergences, the number of generations, and population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Paja c Zivkovi c et al ( 2020) reported that the first H. minuta and H. flava adults flew at end of March in Croatia, Zagreb in 2019. However, in Lithuania, the white sticky traps caught the first H. minuta and H. flava adults one month later presumably due to the lower annual temperatures between 2010-2012(Tamo si unas et al, 2014. In terms of the first adult catch in the same year (Pom az 2015, Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The most important aim of integrated pest management (IPM) is to spatiotemporally predict the existence of pests to determine efficient insecticide delivery timing (Lefebvre et al, 2015). So far only the chromotropic white sticky trap is available to monitor the flight activity of these two sawfly species in plum orchards (Blaisinger, 1975;Tamo si unas et al, 2014). Although H. minuta and H. flava are present in Hungarian plum orchards, little is known about their populations' size, flight dynamics and distribution of the different species.…”
Section: Introductionmentioning
confidence: 99%